Acute improvement of aortic mechanics following hemodialysis in patients with chronic renal failure. - Soubassi, L; Tousoulis, D; Antoniades, C; Lambrou, S; Aggeli, C; Chaniotis, D; Soubassi, S; Pitsavos, C; Stefanadis, C; Soubassis, P; Toutouzas, P (2006)
BACKGROUND: Evidence suggests that distensibility of the aorta is decreased in patients with end-stage renal failure, while the underlying mechanisms are unclear. HYPOTHESIS: The purpose of the study was to evaluate the distensibility of the aorta in patients at the end stage of chronic renal failure before and after hemodialysis (HD). METHODS: The diameter of the ascending aorta and distensibility were assessed in 48 patients on HD (31 men, 17 women, aged 45+/-14 years) and in 27 normal subjects (17 men, 10 women, aged 44+/-14 years). The diameter of the aorta was evaluated by M-mode in the parasternal long-axis view. RESULTS: Aortic distensibility was significantly lower in patients on HD before HD (1.9+/-0.7 cm(2) x dyn(-1) x 10(-6)) than in normal control subjects (3.8+/-1.0 cm(2) x dyn(-1) X 10(-6), p< 0.0001). After dialysis, it increased to 2.6+/-1.2 (p < 0.05 compared with baseline, p < 0.001 compared with controls). The change of aortic distensibility correlated with age (R(2) = 0.629 p < 0.001) and ultrafiltration volume (R(2) = 0.168, p < 0.01). CONCLUSIONS: Aortic distensibility in patients with end-stage renal disease is significantly lower than in normal subjects, and it is significantly improved after HD.